Marketing Analysis Of Watermelon (Citrullus Vulgaris) In Pesisir Barat District Of Lampung Province - Enni Asista; Gita Mulyasari; Bambang Sumantri (UNIVED Press, Dehasen University Bengkulu, 2022)
Marketing is a social managerial process by which individuals and groups obtain what they need and want through creating, offering and exchanging products of value with others. This study aims to analyze marketing channels, margins, . and factors that influence the marketing margin of watermelon in Pesisir Barat Regency, Lampung Province. This study uses descriptive analysis and multiple linear regression models involving 56 farmers and 30 watermelon traders. The results of the study show, There are three marketing channels for watermelon in Pesisir Barat Regency, including Channel I (Farmers – Collectors – wholesalers – consumer retailers), channel II (Farmers – Wholesalers – Retailers – Consumers), and channel III (Farmers – Collectors – Retailers – Consumers). The marketing margin on channel I is the highest compared to channels II and III. The price at the producer level is the factor that influences the marketing margin of watermelon (Citrullus Vulgaris) in Pesisir Barat Regency. In contrast, sales volume and marketing costs do not affect watermelon's marketing margin.